Clonal behaviour of myogenic precursor cells throughout the vertebrate lifespan - Hughes, SM; Escaleira, RC; Wanders, K; Koth, J; Wilkinson, DG; Xu, Q (Company of Biologists, 2022)
To address questions of stem cell diversity during skeletal myogenesis, a Brainbow-like genetic cell lineage tracing method, dubbed Musclebow2, was derived by enhancer trapping in zebrafish. It is shown that, after initial formation of the primary myotome, at least 15 muscle precursor cells (mpcs) seed each somite, where they proliferate but contribute little to muscle growth prior to hatching. Thereafter, dermomyotome-derived mpc clones rapidly expand while some progeny undergo terminal differentiation, leading to stochastic clonal drift within the mpc pool. No evidence of cell-lineage-based clonal fate diversity was obtained. Neither fibre nor mpc death was observed in uninjured animals. Individual marked muscle fibres persist across much of the lifespan indicating low rates of nuclear turnover. In adulthood, early-marked mpc clones label stable blocks of tissue comprising a significant fraction of either epaxial or hypaxial somite. Fusion of cells from separate early-marked clones occurs in regions of clone overlap. Wounds are regenerated from several local mpcs; no evidence for specialised stem mpcs was obtained. In conclusion, our data indicate that most mpcs in muscle tissue contribute to local growth and repair and suggest that cellular turnover is low in the absence of trauma.